2021
DOI: 10.1029/2021jd035049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stratospheric Aerosol Injection Geoengineering on the Summer Climate Over East Asia

Abstract: The United Nations Framework Convention on Climate Change (UNFCCC), which has been ratified by >190 countries worldwide, aims to limit global warming to <2°C above the preindustrial level. However, the fact that it is difficult to achieve the national CO 2 mitigation target encourages us to search for alternatives. The solar radiation modification (SRM) geoengineering, which is defined as a measure to temporarily reduce or offset global warming by changing the albedo of the Earth system and increasing the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The dynamic term that is primarily associated with altered atmospheric circulations is modified by horizontal and vertical velocity anomalies. The moisture budget analysis has been widely used to investigate precipitation variations and relevant physical processes in preceding simulated studies (e.g., Chen et al, 2020; D'Agostino et al, 2019; Liu et al, 2021; Tian et al, 2022; Wu et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic term that is primarily associated with altered atmospheric circulations is modified by horizontal and vertical velocity anomalies. The moisture budget analysis has been widely used to investigate precipitation variations and relevant physical processes in preceding simulated studies (e.g., Chen et al, 2020; D'Agostino et al, 2019; Liu et al, 2021; Tian et al, 2022; Wu et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…SAI modeled using Stratospheric Aerosol Geoengineering Large Ensemble (GLENS) models at a level to compensate for changes in temperature was shown to overcompensate for precipitation, changing drought risk over major river basins in Africa (Abiodun et al, 2021). Other work has found SAI can change the drought pattern over East Asia (Liu et al, 2021). Work examining SRM with a uniform solar reduction has found that, with globally varying effectiveness, SAI may reduce the likelihood of drought by reducing the frequency of heatwaves and consecutive dry days (Dagon and Schrag, 2017).…”
Section: Monsoons and Tropical Stormsmentioning
confidence: 96%
“…Although increasing attention has recently been given to the SAI‐induced changes in the monsoon system (Da‐Allada et al., 2020; Liu et al., 2021; Pinto et al., 2020), the response of the EAWM to the SAI remains unknown. The analysis of solar dimming (solar constant reduction) experiments can provide insights on the potential climate response to SAI.…”
Section: Introductionmentioning
confidence: 99%